2015
DOI: 10.2134/agronj15.0102
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of CERES–Sorghum as Implemented in the Cropping System Model Version 4.5

Abstract: Sorghum [Sorghum bicolor (L.) Moench] is the fi ft h most important grain crop globally. It stands out for its diversity of plant types, end-uses, and roles in cropping systems. Th is diversity presents opportunities but also complicates evaluation of production options, especially under climate uncertainty. Ecophysiological models can dissect interacting eff ects of plant genotypes, crop management, and environment. We describe the sorghum module of the Cropping System Model (CSM) as implemented in the Decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 36 publications
3
51
0
Order By: Relevance
“…The effects of elevated CO 2 on RUE are modeled empirically using curvilinear multipliers based on a lookup function to fit crop responses to CO 2 concentration. The potential daily biomass production per plant, PCARB, is calculated using the following equation (White et al, 2015):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of elevated CO 2 on RUE are modeled empirically using curvilinear multipliers based on a lookup function to fit crop responses to CO 2 concentration. The potential daily biomass production per plant, PCARB, is calculated using the following equation (White et al, 2015):…”
Section: Methodsmentioning
confidence: 99%
“…The CERES-Sorghum model was enhanced to simulate the effect of elevated CO 2 on the potential evapotranspiration by increasing stomatal resistances in the Penman-Monteith equation (Acock and Allen, 1985;Allen et al, 1987). More detailed information about the CERES-Sorghum model has been described previously (White et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The CERES-Sorghum Model CERES-Sorghum (Alagarswamy and Ritchie, 1991;White et al, 2015) is the sorghum growth module of the Decision Support System for Agrotechnology Transfer cropping system model (DSSAT-CSM) (Jones et al, 2003;Hoogenboom et al, 2017). As described in greater detail in Jones et al (2003), the DSSAT-CSM is an integrated collection of software components that includes a main program, management module, soil module, weather module, and a soil-plant-atmosphere module.…”
Section: Methodsmentioning
confidence: 99%
“…Each crop growth module requires environmental data, genetic and ecotype parameters, and crop management parameters as inputs. A more complete description of the CERES-Sorghum growth module, and its ability to reproduce sorghum phenology, yield variation, and management effects found in field studies can be found in White et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Though there were no radiation use efficiency (RUE) data available for tef, it was assumed that, as a C4 crop, tef would have a higher RUE than wheat. Models for the C4 crops maize, millet, and sorghum all have higher aboveground RUE values than wheat models [20,[44][45][46]. In order to calculate the DSSAT-Tef aboveground RUE, the percent difference between the DSSAT-CERES-Wheat and DSSAT-Sorghum aboveground RUE was used to estimate the ratio RUE ratio between wheat and a C4 crop.…”
Section: Growthmentioning
confidence: 99%